Fatigue severity scale, fibromyalgia impact questionnaire, and visual pain scale scores in patients with fibromyalgia (Annals of Medical Research, 2021)
None
Keywords: Fibromyalgia (FM), antinuclear antibody (ANA), fatigue severity scale (FSS), FM impact questionnaire (FIQ), and visual pain scale (VAS)